2001
DOI: 10.1021/ja003850n
|View full text |Cite
|
Sign up to set email alerts
|

Single-Site β-Diiminate Zinc Catalysts for the Alternating Copolymerization of CO2 and Epoxides:  Catalyst Synthesis and Unprecedented Polymerization Activity

Abstract: Synthetic routes to zinc beta-diiminate complexes are reported. The synthesis of 11 beta-diimine [(BDI)-H] ligands, with varying N-aryl substituents and bridging structures, is described. These ligands are converted to (BDI)ZnX complexes (X = OAc, Et, N(SiMe3)2, Br, Cl, OH, OMe, O(i)Pr). X-ray structural data revealed that all zinc complexes examined exist as micro-X-bridged dimers in the solid state, with the exception of the zinc ethyl and amido complexes which were monomeric. Complexes of the form (BDI)ZnOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
410
2
8

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 546 publications
(454 citation statements)
references
References 62 publications
28
410
2
8
Order By: Relevance
“…Complex 1a shows a crystallographic inversion center whereas 1b displays a crystallographically imposed C 2 axis. The C 3 N 2 Zn rings in both 1a and 1b are almost planar with the Zn atoms slightly out of the plane, as was previously observed in [Mes nacnacZn(µ-H)] 2 [5], DippnacnacZnH [7], DippnacnacZnN(SiMe 3 ) 2 [13], and DippnacnacZn(µ-H) 2 BH 2 [14]. In 1a, the almost planar C(CN) 2 Zn six-membered rings adopt a co-planar orientation, whereas in 1b the rings are twisted by 42.6 • as was observed for [Mes nacnacZn(µ-H)] 2 [5].…”
Section: Resultssupporting
confidence: 75%
“…Complex 1a shows a crystallographic inversion center whereas 1b displays a crystallographically imposed C 2 axis. The C 3 N 2 Zn rings in both 1a and 1b are almost planar with the Zn atoms slightly out of the plane, as was previously observed in [Mes nacnacZn(µ-H)] 2 [5], DippnacnacZnH [7], DippnacnacZnN(SiMe 3 ) 2 [13], and DippnacnacZn(µ-H) 2 BH 2 [14]. In 1a, the almost planar C(CN) 2 Zn six-membered rings adopt a co-planar orientation, whereas in 1b the rings are twisted by 42.6 • as was observed for [Mes nacnacZn(µ-H)] 2 [5].…”
Section: Resultssupporting
confidence: 75%
“…Coates and his coworkers [23][24][25][26][27] have reported that zinc bis(␤-diiminates) (4) are more active than Darensbourg's zinc bis(phenoxides) (1) for the alternating copolymerization of carbon dioxide and cyclohexene oxide. The zinc bis(␤-diiminates) (4) were dimeric in the solid state, as shown by X-ray crystallographic analysis, 23 whereas the 1 H NMR data showed that 4 was monomeric in solution.…”
Section: Copolymerization By Zinc ␤-Diiminatesmentioning
confidence: 99%
“…A series of compounds with various organic groups bound to zinc, i.e. 181 266 , 182 267 , 183 266 , 184 266 and 185 268 ( Figure 90), have been prepared and were structurally characterized in the solid state. All compounds have comparable structural features.…”
Section: E Monoorganozinc Compounds Rzny With Y = Nrmentioning
confidence: 99%